Modus operandi of agricultural and livestock producers’ organizations in Risaralda, Colombia. First phase: Methodological adaptations and some results (2017)
Purpose: This empirical project is currently underway. Its purpose is to analyze the way in which 19 agricultural producers’ associations and cooperatives of Risaralda operate in terms of the structure and content of each organization, as well as their strategies of commercial distribution and pricing. Themes: For the study, these 19 selected objects of study are taken as interorganizational arrangements, which in turn institute networks between them. Development: The sample is composed by 298 members of the 19 organizations previously mentioned, to whom a survey is applied; and by the legal representatives of the same entities, who are given a semi-structured interview. Conclusions: The first findings show that the majority of these organizations have developed searching to improve their negotiation conditions vis-à-vis third parties, mainly clients or commercial intermediaries, suppliers and state agents. Faced with the latter, interest in being linked to the Ministry of Agriculture’s Support Program for Productive Partnerships has emerged. The program is operated through the Department of Agriculture of each municipality.